Legal Status of Consuming Swiftlet Meat in the Perspective of Hanafi and Shafi’i Scholars: A Case Study of Selambo Village, Percut Sei Tuan District, Deli Serdang Regency - Lubis, Muhammad Raihan; Hayati, Amal (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study analyzes the legal ruling on the consumption of swiftlet meat according to the perspectives of Hanafiyah and Shafi’iyah scholars. Examining these two viewpoints is expected to provide a new contribution as well as broaden public understanding of the issue. The divergence of opinions between the two schools regarding the permissibility of consuming swiftlet meat is based on various considerations, thereby necessitating a more in-depth examination through scholarly research. The research adopts a library-based approach (library research), utilizing theories and arguments drawn from relevant and supporting literature. In addition, it is complemented by field research aligned with the selected object of study, in order to enrich the analysis and strengthen the findings. The results reveal that, according to Hanafiyah scholars, consuming swiftlet meat is deemed permissible (halal), as the bird is considered tame and harmless to humans. Conversely, Shafi’iyah scholars rule it as impermissible (haram). [Penelitian ini menganalisis hukum mengonsumsi daging burung walet menurut pandangan ulama Hanafiyah dan Syafi’iyah. Kajian terhadap kedua pandangan tersebut diharapkan dapat memberikan kontribusi baru sekaligus memperluas pemahaman masyarakat mengenai isu ini. Perbedaan pendapat antara kedua mazhab terkait konsumsi daging burung walet didasarkan pada alasan yang beragam, sehingga perlu dikaji secara lebih mendalam melalui penelitian ilmiah. Jenis penelitian yang digunakan adalah penelitian kepustakaan (library research) dengan memanfaatkan teori-teori dari literatur yang relevan dan mendukung topik penelitian. Selain itu, penelitian ini juga dilengkapi dengan penelitian lapangan yang disesuaikan dengan objek yang dipilih, guna memperkaya analisis dan memperkuat hasil kajian. Hasil penelitian menunjukkan bahwa menurut ulama Hanafiyah, hukum mengonsumsi daging burung walet adalah halal, karena burung tersebut dianggap jinak dan tidak membahayakan manusia. Sebaliknya, menurut ulama Syafi’iyah, hukumnya adalah haram.]